PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN STANDAR AKUNTANSI PEMERINTAH DAN PERAN INTERNAL AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Empiris Pada SKPD Kabupaten Demak) - Adrian Farros Elfauzi; Sudarno Sudarno (Diponegoro Journal of Accounting, 2019)
This study aims to examine the factors that influence the quality of regional financial reports in the Demak District SKPD. As well as knowing the efforts made by the Government of Demak Regency to obtain fair opinions without exceptions. These efforts need to get appreciation from local government officials. The aim of this Government is to improve the reliability of the quality of the financial statements produced, especially in terms of asset management.The sample used in this study were 141 respondents with purposive sampling technique in Demak Regency. Data was obtained by distributing questionnaires. Questionnaires returned were 138 questionnaires. Data analysis used is test instrument, descriptive statistics, classical assumption test and hypothesis test.The results showed that the competence of human resources had a significant positive effect on the quality of financial statements, while government accounting standards, did not affect the quality of financial reports and the role of internal audit had a significant negative effect on the quality of financial statements.